REPRESENTASI SUARA PEREMPUAN URBAN DALAM NOVEL HOME SWEET LOAN KARYA ALMIRA BASTARI : ANALISIS WACANA KRITIS MODEL SARA MILLS - Mega Adriyanti; Faizah Fitri (Jurnal PENEROKA, 2026)
This study aims to analyze the representation of urban women's voices in Almira Bastari's novel Home Sweet Loan through Sara Mills' critical discourse analysis approach. This study focuses on three main aspects of Mills' model, namely the position of the subject, the position of the object, and the position of the reader to reveal how power relations, gender stereotypes, and resistance are represented in the text. The method used is descriptive qualitative with discourse analysis techniques. The results show that women in this novel are portrayed as rational and critical subjects, especially in financial management and life decision-making, which simultaneously reverses the stereotype of women as consumptive figures. However, at the same time, women remain in a vulnerable position due to domestic pressures, demands for family obedience, and social expectations regarding marital status and the image of the ideal family. An interesting finding from this study is that patriarchal values are not only depicted through male characters, but also reproduced by female characters from previous generations. Through the reader's position, the text directs empathy towards female characters while encouraging readers to criticize of gender inequality in contemporary urban life.